Estimating the shadow economy in Jordan: causes, consequences, and policy implications - Alkhdour, Rajeh, author; Bernasek, Alexandra, advisor; Fan, Chuen-mei, committee member; Pena, Anita Alves, committee member; Yasar, Gamze, committee member (Colorado State University. Libraries, 2011)
Economists have been paying increasing attention to the study of the shadow economy in many developed and developing countries in recent years. This attention is due to the consequences and the policy implications related to the shadow economy. Due to the unobserved and hidden nature of the shadow economy, it is difficult to get accurate estimates of its size. However, there are some techniques that have been used by economists to indirectly estimate the size of the shadow economy. This dissertation estimates the annual size of the shadow economy in Jordan during the period 1976-2010 using two methodologies: the currency approach and the multiple indicators multiple causes (MIMIC) approach. It also analyzes the economic consequences and the policy implications of the shadow economy, estimating the amount of tax evasion in Jordan during the aforementioned time period. This is the first study that differentiates the effect of taxes on imports (custom duties) on the shadow economy from the effect of other taxes (income and sales taxes). It hypothesizes, unlike other studies, that taxes on imports negatively affect the size of the shadow economy. The currency approach results are consistent with this hypothesis. This study is also the first one to take into consideration religious factors as one of the determinants of the demand for money in circulation which is used in the currency approach to estimating the shadow economy. It is hypothesizes that the number of Islamic banks in Jordan negatively affects the demand for money in circulation. The coefficient of this variable has a negative sign, which is consistent with this hypothesis; however, this variable is insignificant at the 10 percent level. The other determinants of the demand for money in circulation in Jordan are: the effective tax rate on sales, the effective income tax rate, the effective tax rate on imports, the weighted average of interest rates on savings, and a dummy variable for the depreciation of the Jordanian dinar in 1988. According to the MIMIC approach, the causal variables for the shadow economy in Jordan are found to be: the total effective tax rate (tax revenues/GDP), the unemployment rate, the extent of government regulation (government intervention in the economy), and depreciation of the Jordanian dinar in 1988. The growth rate of real GDP and the growth rate of real private consumption are found to be indicators of the shadow economy in Jordan. The MIMIC approach results are consistent with previous studies that have found taxes and regulations to be the main causes of the shadow economy. The results also support the hypothesis that the depreciation of the Jordanian dinar in 1988 has a positive effect on the shadow economy in Jordan. The unemployment rate is found to have a negative effect on the shadow economy in Jordan. This indicates that the income effect of unemployment is greater than the substitution effect. In this dissertation, the main consequences and the policy implications of the shadow economy are analyzed. Tax evasion in Jordan is estimated for the period of study based on the results of the currency demand and the MIMIC approaches. It has been shown that the shadow economy has a distorting effect on the accuracy of a country's national accounts statistics. In addition, some policy recommendations are presented to reduce the distorting impact of the shadow economy. Taking into consideration the existence of the shadow economy when conducting the economic policy will increase the efficiency of this policy. There is a need for further research into the impact of the shadow economy on some economic policy issues in Jordan.
Keywords: shadow economy; underground economy